Identification of novel SNPs associated with risk and prognosis in patients with castration-resistant prostate cancer. (December 2016) - Sissung, Tristan M; Deeken, John; Leibrand, Crystal R; Price, Douglas K; Ehrlich, Sheryl; Steinberg, Seth M; Liewehr, David J; Dahut, William; Figg, William D
Aim: Metabolism and transport play major roles in life-long exposure to endogenous and exogenous carcinogens. We therefore explored associations between polymorphisms in absorption, distribution, metabolism and elimination genes and the risk and prognosis of castration-resistant prostate cancer (CRPC).Materials & methods: A total of 634 genotypes were tested in 74 patients using the Affymetrix DMETv1.0 platform.Results: No relation to risk was found. Three SNPs were associated with CRPC prognosis in Caucasians: ABCB11 rs7602171G>A (p = 0.003; n = 30; hazard ratio [HR]: 0.307), GSTP1 rs1799811C>T (p = 0.001; n = 38; HR: 0.254) and SLC5A6 rs1395 (p = 0.004; n = 35; HR: 3.15). Two other polymorphisms among Caucasians were associated with interesting trends: ABCB4 rs2302387C>T (p = 0.039) and ABCC5 rs939339A>G (p = 0.018).Conclusion: This exploratory study is the first to show that polymorphisms in several absorption, distribution, metabolism and elimination genes may be associated with CRPC prognosis.